Makna Pesan Podcast Suara Berkelas Episode “Cara Menjadi Manusia Disiplin dan Percaya Diri dalam 40 Menit” terhadap Pembentukan Kepercayaan Diri Pendengar - Dastin Abyan Pradipta; Amiruddin Saleh; Harvia Atika Zahira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of digital technology has changed communication patterns through the presence of podcasts as an educational and motivational medium for listeners. This study aims to determine how listeners interpret messages about discipline and self-confidence, identify key messages that are considered influential, and analyze the role of the Suara Berkelas podcast episode